2020
DOI: 10.1371/journal.pone.0229579
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation study of caregiver perceptions of the Ontario’s Health Links program

Abstract: IntroductionIn 2012, the Ontario government launched Health Links (HL), which was designed to integrate care for patients with multimorbidity and complex needs who are high users of health services. This study evaluated perceptions of family and friend caregivers of patients enrolled in the HL program. Research questions included: What are (a) characteristics of caregivers of patients enrolled in HL (b) caregivers' perceptions of the program in relation to HL's guiding principles (patient and family-centred ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We observed that some caregivers felt their needs were less important than the patients which is consistent with other literature that suggests caregivers may be reluctant to voice their own needs [39]. While caregiving can be rewarding, existing qualitative studies have demonstrated that caregivers' health and wellbeing can be negatively impacted, highlighting the necessity of tailored community supports and resources [40]. Such supports may include ensuring caregivers know they are able to use the 24/7 support line for questions, access to peer support, and e-learning resources [41].…”
Section: Discussionsupporting
confidence: 88%
“…We observed that some caregivers felt their needs were less important than the patients which is consistent with other literature that suggests caregivers may be reluctant to voice their own needs [39]. While caregiving can be rewarding, existing qualitative studies have demonstrated that caregivers' health and wellbeing can be negatively impacted, highlighting the necessity of tailored community supports and resources [40]. Such supports may include ensuring caregivers know they are able to use the 24/7 support line for questions, access to peer support, and e-learning resources [41].…”
Section: Discussionsupporting
confidence: 88%
“…Caregivers' needs include: f) providing system navigation and an easily retrievable hard copy list of relevant health and community services to support patients and their caregivers, and g) offering more patient support to reduce caregiver burden (7).…”
Section: Introductionmentioning
confidence: 99%
“…This unpredictable and worldwide situation has emphasized the role of FCG in our health care system with a risk on their own psychosocial and health negative issues. Thus, the lack of consideration of FCGs has important implications for the health care system [ 14 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This context then underlines the need to take into consideration the role of the FCGs [ 33 , 34 ] and the obstacles they are facing [ 32 ], with regard to their physical and mental health. The 3S provides answers for some social issues encountered by FCGs, but not for all of their concerns.…”
Section: Discussionmentioning
confidence: 99%